Extended Partial Orders: A Unifying Structure for Abstract Choice Theory - Klaus Nehring; Selva Demiralp; Clemens Puppe (University of California, Department of Economics, 1997)
The concept of a strict extended partial order (SEPO) has turned out to be very useful in explaining (resp. rationalizing) non-binary choice functions. The present paper provides a general account of the concept of extended binary relations, i.e., relations between subsets and elements of a given universal set of alternatives. In particular, we define the concept of a weak extended partial order (WEPO) and show how it can be used in order to represent rankings of opportunity sets that display a ""preference for opportunities."" We also clarify the relationship between SEPOs and WEPOs, which involves a non-trivial condition, called ""strict properness."" Several characterizations of strict (and weak) properness are provided based on which we argue for properness as an appropriate condition demarcating ""choice based"" preference.
Keywords: 330